A Simple Synthesis of Alkyl 2-Aminobenzo[b]thiophene-3-carboxylates via an Unexpected Dehydrogenation of Alkyl 2-Amino-4,5,6,7-tetrahydrobenzo[b]thiophene-3-carboxylates - Adib, Mehdi; Bayanati, Maryam; Soheilizad, Mehdi; Ghazvini, Helia Janatian; Tajbakhsh, Mahmood; Amanlou, Massoud (Synlett, 2014)
A simple method for the preparation of alkyl 2-aminobenzo[b]thiophene-3-carboxylates is described. Alkyl 2-amino-4,5,6,7-tetrahydrobenzo[b]thiophene-3-carboxylates, generated from the Gewald three-component reaction between cyclohexanones, alkyl cyanoacetates and sulfur, undergo dehydrogenation in benzonitrile under an air atmosphere to afford alkyl 2-aminobenzo[b]thiophene-3-carboxylates in good to excellent yields.
Keywords: 2-aminobenzo[b]thiophene-3-carboxylates; Gewald reaction; cyclohexanones; cyanoacetates; benzonitrile; dehydrogenation; heterocycles